CHALLENGES IN WRITING HORTATORY EXPOSITION TEXT EXPERIENCED BY TENTH GRADE STUDENTS OF MADRASAH ALIYAH - Batubara, Sarnita (BRIGHT VISION Journal of Language and Education, 2024)
The objective of this research to find out challenges in writing Hortatory Exposition Text experienced by tenth grade students of Madrasah Aliyah . This research took the population of the students at X MA NahdatulUlamaBatang Toru in academic year 2022/2023.  The researcher take X grade which the students are 15 people; they are 5 males and 10 females. This research used qualitative research with descriptive method of research, because the researcher aimed to know students challenges in writing hortatory exposition text. The result showed that 15 students explain the challenges in writing hortatory text. Almost all of the students had challenges in some points 1) They have the challenges in learning English such such as have a limited vocabulary, or tenses. 2) Understanding the generic structure of Hortatory text such as can not distinguish between report and hortatory text based on it’s generic structure. 3) Develoving the paragraph. They tend to get confused how to develop the paragraph.